PUBLIC TRANSPORTATION RESPONSIBILITY TO PASSENGERS NOT RECOGNIZED ON A TRANSPORT COMPANY WHO GET LOSS - Hendro Nasrian; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Transportation facilities are an important factor in realizing the smooth process in organizing the transportation of people by public transport. The importance of these means of transportation can be reflected in the increasing need for public transport services, especially in big cities, the need for public transport services as if it has become part of the urban community who do not have their own vehicle.Problems and objectives to be discussed in this thesis is to know how the rights and obligations of the carrier in transporting passengers with the travel services as a public transport service entrepreneurs and To know the extent of the responsibility of the carrier to passengers who are not recorded on the agency who suffered losses. The location of the research is conducted on public transportation in Rengat City, Indragiri Hulu Regency. Research is focused on the existing travel in Rengat City.The type of this research is sociological research, while the nature of the research is descriptive. Sources of data in this study obtained through primary data and secondary data. Data collection techniques conducted in this thesis using interviews and literature review while the author data analysis techniques do with qualitative methods.Having described and discussed in this thesis, it can be concluded and suggested that the responsibility of public transport to passengers who are not recorded on the agency that suffered losses is the presumption responsibility that the company will provide compensation in accordance with Law No. 33 of 1964 and Law No. 34 Year 1964 junto Government Regulation No. 17 of 1965 and Government Regulation Number 18 Year 1965 on the amount of compensation. According to the principle of liability under the presumption of liability, the carrier shall always be held liable for any loss arising from the transport carried. But if the carrier can prove that he is not guilty, then he is exempt from the obligation to pay compensation. The meaning of "innocent" is not to do negligence, has taken the necessary action to avoid any losses or incidents that cause unavoidable unavoidable.Keywords: Responsibility - Public transport - Unofficial - Consumer